Influence of energy drink consumption on perceived quality of life in young adults and adult population - Otero-Requeijo, Miriam; Veiga-Rodeiro, Sergio; Belda-Ferri, Lorena; Villanueva-Blasco, Víctor José (Frontiers in Nutrition, 2025)
BackgroundEnergy drink (ED) use is common among young adults and adult populations and may be linked to poorer quality of life (QoL). This study examined the prevalence of ED consumption and its association with QoL in Spanish adults.MethodA cross-sectional design was used with a sample of 1,146 participants aged 18 to 54 years, recruited by convenience sampling through university mailing lists and social media. The web-based questionnaire collected self-reported their energy drink and other substance use and their quality of life (WHOQOL-BREF). Multivariable linear and ordinal logistic regressions were stratified by sex (given a significant sex×ED interaction) and adjusted for age, living arrangement, education, occupation, self-rated health, and past-month use of alcohol, tobacco, and cannabis.ResultsAmong 1,146 participants, ED use was 62.7% ever, 21.3% past 30 days, and 5.7% daily. Although most associations were not statistically significant, point estimates suggested lower QoL among ED consumers. In men, daily ED use was associated with lower psychological (mental health) domain scores (β = −8.72; 95% CI − 17.00 to −0.45; p = 0.039). In women, daily ED consumers had higher odds of perceiving a less healthy environment (OR = 2.58; 95% CI 1.28–5.17; p = 0.008). Additional item-level analyses indicated higher odds of negative mood (men: OR = 3.53; 95% CI 1.28–9.75; p = 0.015) and dissatisfaction with self (men: OR = 2.71; 95% CI 1.07–6.89; p = 0.036) among daily users.ConclusionED consumption is associated with poorer QoL indicators, particularly mental health in men and environmental perceptions in women. Findings support targeted prevention and proportionate regulation (e.g., labeling, marketing oversight), with attention to sex and age profiles within adult populations.